Molecular Orbital Theory of the Electronic Structure of Organic Compounds IV : A CNDO/S-CI SCF MO Study on the Lower Electronic States of Large Molecules. Singlet-triplet Transitions of Dioxodiazacycloalkanes - Grinberg, Horacio (1982)
The semiempirical molecular orbital CNDO/S-CI spectral parameterization has been used to elucidate the lower triplet electronic states of a series of dioxodiazacycloalkanes. The 1³B₂(nₒπ*) and 1³A₂ (nₒπ*) triplet spectroscopic states involve intramolecular charge transfer from the oxygen to the carbon atom of the carbonyl group, which is supported by electron density calculations of these excited states. The solvation energy was incorporated in the calculations.